Retail Flower Shop Operation and Management. A Teacher's Manual - Stinson, Richard F.; Pennsylvania State Univ., University Park. Pennsylvania Agricultural Experiment Station ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Field tested by teachers attending an institute in landscape horticulture July 5-22, 1966, this teacher's manual is one of a series of instructional aids developed by the Department of Agricultural Education at the Pennsylvania State University. The content includes problem areas of: (1) Exploring Occupational Opportunities in the Retail Flower Shop Business, (2) Uses and Characteristics of Flowers, Plants, and Decorative Materials, (3) Designing with Flowers and Decorative Materials, (4) Using Flower Arrangements, (5) Merchandising and Selling, and (6) Retail Flower Shop Management. In addition to the student material contained in VT 007 271, this document incorporates at the end of each unit suggestions and references for the teacher, suggested learning activities, suggested placement experiences, and a sample test. The material was developed for schools near large centers of population for use in team teaching involving the teacher of agriculture, a business teacher, and a distributive education teacher. Course length may vary from 6 weeks to 1 semester with students of upper high school or post high school level, who are interested in entering careers in retail flower shops and who have opportunity for occupational work experience in floriculture. A course examination is included. (DM)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Div. of Adult and Vocational Research.
Contract Number: OEC-5-85-014.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administration; Agricultural Education; Floriculture; Marketing; Ornamental Horticulture Occupations; Reference Materials; Salesmanship; Teaching Guides; Vocational Education